Embedded business librarianship for the public librarian - Alvarez, Barbara, 1989- (ALA Editions, an imprint of the American Library Association, 2016)
By leaving the physical library space and becoming integrated within the business community, librarians will cultivate awareness of the library's resources and expertise while becoming part of the dialogue of the business community. Alvarez shows that by reaching out to the business owners, professionals and job seekers you serve, they will be attracted into the library, allowing a vital business community collaboration.